2016
DOI: 10.1002/bmb.21033
|View full text |Cite
|
Sign up to set email alerts
|

A unique large‐scale undergraduate research experience in molecular systems biology for non‐mathematics majors

Abstract: Systems biology is frequently taught with an emphasis on mathematical modeling approaches. This focus effectively excludes most biology, biochemistry, and molecular biology students, who are not mathematics majors. The mathematical focus can also present a misleading picture of systems biology, which is a multi-disciplinary pursuit requiring collaboration between biochemists, bioinformaticians, and mathematicians. This article describes an authentic large-scale undergraduate research experience (ALURE) in syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…An additional complicating factor is that BioSB research and education are typically embedded in biology or computer science departments, or within medical centres. Combining systems biology and bioinformatics into one master programme, fits well with developments in the field where both are generally considered integral parts of computational biology ( Bare and Baliga, 2014 ; Kappler et al , 2017 ; Korcsmaros et al , 2013 ; Yang et al , 2009 ). In the Netherlands, at the post-graduate level the Netherlands Consortium for Systems Biology and the Netherlands Bioinformatics Centre merged into the BioSB Research School in 2015 ( www.biosb.nl ) ( van Gelder et al , 2017 ).…”
Section: Discussionmentioning
confidence: 75%
“…An additional complicating factor is that BioSB research and education are typically embedded in biology or computer science departments, or within medical centres. Combining systems biology and bioinformatics into one master programme, fits well with developments in the field where both are generally considered integral parts of computational biology ( Bare and Baliga, 2014 ; Kappler et al , 2017 ; Korcsmaros et al , 2013 ; Yang et al , 2009 ). In the Netherlands, at the post-graduate level the Netherlands Consortium for Systems Biology and the Netherlands Bioinformatics Centre merged into the BioSB Research School in 2015 ( www.biosb.nl ) ( van Gelder et al , 2017 ).…”
Section: Discussionmentioning
confidence: 75%
“…She reported that the sophisticated mathematical modeling done in her area (e.g. modeling of the movement of cells) was primarily done in collaboration with mathematicians , but that “at least an understanding so they could talk to people would be useful.” Other interviews coded for mathematics literacy noted the need to read and interpret articles and understand major developments in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Although SEA-PHAGES represents an outstanding way to introduce authentic collaborative research into the biology classroom, it is not the only way to construct an engaging “-omics”-based laboratory project. Mass spectrometry has been utilized by several groups in the development of engaging “-omics”-based CUREs (course-based undergraduate research experiences) ( 10 12 ); however, this particular SEA-PHAGES-based model shows great promise in its accessibility to institutions limited by budget and infrastructure. Although the generation of mass spectrometry data requires access to an instrument and trained technician to perform the necessary proteomics procedures, advances in technology have brought the costs of this work at many core facilities down to levels that are accessible to most classroom laboratory budgets.…”
Section: Discussionmentioning
confidence: 99%